Spiderweb deformation induced by electrostatically charged insects - Ortega-Jimenez, Victor Manuel (Nature Publishing Group, 2013)
Capture success of spider webs has been associated with their microstructure, ornamentation, and wind-induced vibrations. Indirect evidence suggests that statically charged objects can attract silk thread, but web deformations induced by charged insects have not yet been described. Here, we show under laboratory conditions that electrostatically charged honeybees, green bottle flies, fruit flies, aphids, and also water drops falling near webs of cross-spiders (Araneus diadematus) induce rapid thread deformation that enhances the likelihood of physical contact, and thus of prey capture.